Long-Term Results after Prostate Artery Embolization in Patients with Benign Prostatic Hyperplasia (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Benign prostatic hyperplasia of the prostate gland is a disease caused by the growth of adenomatous tissue in the transition zone of the prostate gland, which is mainly seen in older men. The consequence of BPH is the occurrence of intravesicular obstruction. This study is based on the analysis of the examination and treatment data of 9 patients with BPH treated at the Bukhara Regional Multidisciplinary Medical Center (BRMMC) Bukhara branch of the Republican Specialized Scientific and Practical Medical Center of Urology. Treatment with the PAE method was carried out in 2018-2020 on the basis of the X-ray endovascular department of BRMMC. For long-term outcomes, the study period was 36 months after performing PAE. In the postoperative period, all patients received tamsulosin 0.4 mg, 1 capsule 1 time per day for 1 month. In the early postoperative period, postembolization syndrome was observed, manifested as pain in the perineum, anus, lower part of the vagina, urge to urinate, and pain along the urinary tract. In the postoperative period, diclofenac sodium suppositories were prescribed at a dose of 75 mg rectal at bedtime for 5 days once a day to prevent and relieve pain. The pain syndrome was mild and average up to 3 points.